Hubungan Gaya Kepemimpinan Kepala Madrasah dengan Iklim di MA PP Al-Ikhlas Ujung Bone - Paizal, Irfan; Siraj, Arifuddin; Mania, Sitti (El-Idare, 2020)
This research strive to present relationship of leadership style of headmaster with madrasah climate. This research aims to: 1) describe the reality of leadership style of headmaster; 2) describe the reality madrasah climate; and 3) examine the correlation between leadership style of headmaster and madrasah climate at MA PP Al-Ikhlas Ujung Bone. This research is a quantitative by ex post facto method. Instrument used is a questionarre than analyzed by using product moment correlation. This research indicate that: 1) leadership style of headmaster including the good category with percentage of 82,25%; 2) madrasah climate including the high category with percentage of 80,5%; and 3) the correlation between leadership style of headmaster and madrasah climate indicate a positive correlation with correlation coefficient value at 0,643.